2016
DOI: 10.1186/s13098-016-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased depression and metabolic risk in postmenopausal breast cancer survivors

Abstract: Objective: Breast cancer survivors (BCS) are at high risk for the development of obesity, type 2 diabetes mellitus, and metabolic syndrome. There is increasing interest in the association between depression and metabolic dysfunction, which is relevant in this population as depression is often present in the chronic phase of cancer recovery. Thus, the aim of this study was to evaluate metabolic risk in BCS with and without depression compared to non-cancer controls.Methods: African American (46 %) and Caucasian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A recent meta-analysis showed, in fact, that chemotherapy leads to a body weight increase of 2.7 kg on average (95% Confidence Interval [CI] 2.0–7.5 kg), with a significant degree of variation due to high heterogeneity between studies 13 . The pathophysiology of weight gain during chemotherapy has not been fully elucidated and is believed to have a multifactorial etiology: among these potential contributors there are premenopausal status at breast cancer diagnosis 14 , fatigue and reduced physical activity 17 – 19 along with the consequent reduction in lean body mass and resting energy expenditure 17 , 18 , increased food intake due to treatment-related appetite 19 , common use of steroids 20 and anti-depressant drugs 21 during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed, in fact, that chemotherapy leads to a body weight increase of 2.7 kg on average (95% Confidence Interval [CI] 2.0–7.5 kg), with a significant degree of variation due to high heterogeneity between studies 13 . The pathophysiology of weight gain during chemotherapy has not been fully elucidated and is believed to have a multifactorial etiology: among these potential contributors there are premenopausal status at breast cancer diagnosis 14 , fatigue and reduced physical activity 17 – 19 along with the consequent reduction in lean body mass and resting energy expenditure 17 , 18 , increased food intake due to treatment-related appetite 19 , common use of steroids 20 and anti-depressant drugs 21 during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Adjusting to life can be especially difficult following breast cancer diagnosis, and as such, depression is one of the most frequently cited psychological disturbances [5]. Though multiple factors contribute to depression, the propensity for weight gain among BCS may be a significant component [6]. Likewise, late-age diagnosis of breast cancer increases the risk for functional impairment and physical inactivity [7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, increased glutamate released from cancer cells can lead to excitotoxicity [8], tissue destruction due to surgery or chemotherapy can lead to inflammation [9,10], and stress caused by cancer diagnosis and treatment can disrupt the hypothalamic-pituitary-adrenal (HPA) axis [11]. Observational studies have shown that metabolic syndrome [12], social support [13,14], severe life difficulties [9], and poor diet quality [15] were also associated with depression in cancer survivors.…”
Section: Introductionmentioning
confidence: 99%